PENEGAKAN HUKUM TERHADAP PELANGGARAN LALU LINTAS TIDAK MENGGUNAKAN SABUK PENGAMAN DI KAWASAN HUKUM POLRES ACEH BARAT - Irsadi Aristora; Muhammad Ikhwan Adabi; Nurmala Sari; Rahmat Jhowanda (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
The violation of not wearing a seat belt is regulated in Article 289 of Law Number 22 of 2009 concerning Traffic and Road Transportation. Based on this article, failure to wear a seat belt while driving will be subject to sanctions. In reality, in the jurisdiction of the West Aceh Police, the level of public compliance with seat belt use remains low, as evidenced by the discovery of people not wearing seat belts when accidents occur in West Aceh, which can lead to the risk of injury from collisions. The lack of attention from law enforcement officers to seat belt violations leads to blatant violations. This study addresses the issue of law enforcement regarding traffic violations of not wearing a seat belt and the obstacles to law enforcement. This study uses empirical legal research using qualitative methods. Data were obtained through interviews with the West Aceh Traffic Police and the West Aceh Transportation Agency, field observations, and literature review. The research results indicate that law enforcement has not been effective. From 2021 to 2023, seat belt violations were only issued with warnings, while in 2024, only 46 (forty-six) violations were issued, recorded in Traffic Police data. This high number of violations was due to the lack of deterrent effect in the previous year. Obstacles to law enforcement include a lack of public awareness and compliance with seat belt use while driving and the inability to cover all outlying areas for enforcement. This research recommends that the police prioritize traffic violations involving non-use of seat belts and enforce strict enforcement, intensify outreach, and collaborate with the West Aceh Regency government to effectively implement surveillance cameras and the operation of electronic ticketing.